Effect of EBR- and EBROG-GFRP laminate on the structural performance of corroded reinforced concrete columns subjected to a hysteresis load. (December 2021) - Karimipour, Arash; Farhangi, Visar
Abstract: The reinforced concrete (RC) columns infiltrated by chloride ions in the marine environment are much vulnerable under seismic loading and corrosion can severely reduce their load-bearing capacity. To improve the load-bearing capacity of RC columns subjected to different load conditions and hazardous environments using glass fibre reinforced polymers (GFRP) have been gained a great deal of attention. Therefore, this paper investigated the seismic behaviour of RC columns strengthened by GFRP laminate exposed to the different rebars corrosion levels. A total of 15 square RC columns were fabricated and tested under the lateral seismic load. A novel wrapping method was employed to perform different longitudinal rebar corrosion at levels of 0%, 5%, 10%, 15% and 20%. To introduce GFRP laminate on the specimens' surfaces, two strengthening techniques were applied: Externally Bonded Reinforcement (EBR) and Externally Bonded Reinforcement on Grooves (EBROG), and the effect of these strengthening techniques on the hysteresis behaviour, energy dissipation, stiffness, ductility, load-bearing capacity, and deformation of specimens were studied. Additionally, new models were developed to predict the ductility, stiffness, and energy absorption of EBR- and EBROG-GFRP strengthened RC columns with various rebar corrosion levels. Results showed that using GFRP laminate improved the maximum load-bearing capacity, stiffness, ductility and energy absorption of corroded RC columns, and these properties were further improved using the EBROG technique. However, the difference between the improvement effect of EBR and EBROG techniques was declined with increasing the longitudinal rebars corrosion level. Additionally, the proposed models with high accuracy could be utilized as an efficient tool to anticipate the ductility, stiffness and energy absorption of EBR- and EBROG-GFRP strengthened RC columns exposed to different rebar corrosion levels.